A modified method for enhancing adsorption capability of banana pseudostem biochar towards methylene blue at low temperature. (June 2019) - Liu, Sen; Li, Jihui; Xu, Shuang; Wang, Mengzhen; Zhang, Yucang; Xue, Xinghua
Graphical abstract: Highlights: A novel phosphomolybdic acid modification was developed. Surface oxygen-containing groups and pore channels were created at low temperature. Low pyrolysis temperature resulted in reducing loss of surface functional groups. The modified biochar pyrolyzed at 200 °C exhibited highest adsorption capacity. In-situ generated carboxylic acids played an important role in adsorption of MB. Abstract: A phosphomolybdic acid promoted oxidative pyrolysis was described for preparation of banana pseudostem biochar. The strategy succeeded to introduce oxygen-containing groups onto the biochar surface at low temperature. In addition, pore channels were created, demonstrated by the SEM images of biochar prepared at 200 °C. Adsorption experiments showed that the biochar pyrolyzed at 200 °C exhibited much better adsorption capability than others pyrolyzed at higher temperatures for methylene blue (MB). The adsorption capability of biochar prepared at 200 °C was enhanced from 87.28 to 146.23 mg/g at 45 °C with phosphomolybdic acid modification. The enhancement of adsorption capacity could be ascribed to the increase of surface oxygen-containing functional groups and pore channels. In-situ generated carboxylic groups during adsorption and desorption played an important role in removal of MB. Adsorption of MB was mainly attributed to hydrogen bonding, electrostatic interactions and cation exchanges.